Dramatic Text Comprehension in Early Adolescence: Validating Assessment Criteria - A.A. Adaskina; A.A. Zaretskaya (Psihologo-Pedagogičeskie Issledovaniâ)
The article discusses the problem of evaluating literary text understanding by teenagers aged 11–12. Theoretical analysis showed that the evaluation and development of dramatic text understanding is the most underestimated problem in pedagogical, philological, and psychological research. The diagnostic assessment «Understanding of Dramatic Texts» consists of two parts. The first part allows you to estimate the level of following reading skills: paratext interpretation; the ability to understand the emotional tone of the work; the ability to «recreate» the image of a literary hero; the ability to disclose the author’s claim. In this part of the study, the material used as the survey basis is presented by Alexander Vampilov’s dramatic work «Date» (1961). The second part of the discussed method is based on the creative transformation task. Aesop’s fable «The Liar» was used as epic text to be made into dramatic texts by the learners. The children’s works analysis allowed us to evaluate the formed within the study framework reading attitudes which are necessary for dramatic text decoding and understanding. We assessed the results in terms of form and content. The diagnostic assessment was conducted in three trial stages. First, we ran and recorded conversations with a reference group, which included 16 specialists in the field of philology and theater. This step allowed us to determine evaluation criteria. Grade 5–6 students took part in the second stage of testing. This stage made it possible to shorten and adapt the questionnaire for working with schoolchildren. In the third stage, the methodology was adapted for written implementation